PERSPEKTIF FETHULLAH GṺLEN TENTANG DIALOG DAN TOLERANSI SEBAGAI RESOLUSI KONFLIK - Ozi Setiadi (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2017)
Conflict can not be avoided if there is no any understanding and mutual understanding of a problem. It causes the appearance of a variety of theories dictated by scholars relates to some efforts that must be carried out by socities in order to resolve the conflict. This writing describes how Fethullah Gulen's perspective as a peace loving-person in developing dialogue and tolerance as a conflict resolution. Gulen argues that dialogue and tolerance are two sides of inseperable coin. Dialogue becomes a media that bridges the cooperation of civilization, brotherhood and mutual understanding between each other, and appreciate the values ​​that are believed together. Dialogue shows non-exclusive moderation form and open to the opinions of various circles. While tolerance becomes a very important media when a dialog can not reach an agreement or understanding, it will be the best way. It happens because the tolerance is a way to refrain from a conflict. Even though the presence of dialogue and tolerance are essential to creating peace, it also has particular obstacles to Muslims. According to Gṻlen, the obstacles are the Muslims’ disagreement with Islam nowdays, and the historical collective memory of non-Muslim and Christians about the bloody tragedy befell them for the treatment of Muslims.